ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KAKAO DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Puspita Puri, Nadia Ayu; Zakaria, Wan Abbas; Rangga, Kordiyana (Indonesian Journal of Socio Economics, 2023)
The purpose of this study was to determine farm income, household income, and the level of household welfare of cocoa farmers in Sungai Langka Village, Gedong Tataan District, Pesawaran Regency. The research was conducted by using simple random sampling method with the number of respondents as many as 51 farmers. The types of data used are primary data and secondary data. The analytical method in this research is descriptive qualitative and quantitative analysis. The results showed that the income of cocoa farming in Sungai Langka Village was Rp.2,855,466.93 per hectare with an R/C ratio over the total cost of 1.44 so that farming was profitable. Cocoa farmer household income is Rp21.475.598,00 which comes from main on farm income, non main on farm income, off farm income, and non farm income. The level of household welfare of cocoa farmers in Sungai Langka Village according to the indicators of the Central Statistics Agency in 2014 was classified as prosperous as many as 44 farmers with a percentage of 86.27%.